2017
DOI: 10.1007/s00262-017-2047-2
|View full text |Cite
|
Sign up to set email alerts
|

An unbiased in vivo functional genomics screening approach in mice identifies novel tumor cell-based regulators of immune rejection

Abstract: The clinical successes of immune checkpoint therapies for cancer make it important to identify mechanisms of resistance to anti-tumor immune responses. Numerous resistance mechanisms have been identified employing studies of single genes or pathways, thereby parsing the tumor microenvironment complexity into tractable pieces. However, this limits the potential for novel gene discovery to in vivo immune attack. To address this challenge, we developed an unbiased in vivo genome-wide RNAi screening platform that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
8
1
Order By: Relevance
“…One of the main mechanisms regulating the escape of cancer cells from innate immunity is the expression of CD47, which interacts with SIRP-α on macrophages to prevent phagocytosis. Shuptrine et al (29) identified 709 genes that selectively regulated adaptive anti-tumour immunity in a syngeneic TNBC model, by developing an unbiased, in vivo , genome-wide RNA interference screening platform. Of the five genes with the greatest impact identified by the screening, CD47 had the greatest impact on the immune regulatory pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main mechanisms regulating the escape of cancer cells from innate immunity is the expression of CD47, which interacts with SIRP-α on macrophages to prevent phagocytosis. Shuptrine et al (29) identified 709 genes that selectively regulated adaptive anti-tumour immunity in a syngeneic TNBC model, by developing an unbiased, in vivo , genome-wide RNA interference screening platform. Of the five genes with the greatest impact identified by the screening, CD47 had the greatest impact on the immune regulatory pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when studied in tumor models in immunocompetent animals, the induction of adaptive immune responses in mediating therapeutic efficacy of CD47 neutralization has been observed [10,11,12,13,14,15,16,17,18]. These studies revealed that CD47 expressed on tumor cells is a key suppressor of antitumor immunity as well as a mediator of resistance to PD1 checkpoint blockade therapy [19,20]. However, it is not clear how CD47 blockade facilitates tumor immunosurveillance.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear how CD47 blockade facilitates tumor immunosurveillance. Several mechanisms have been proposed, including enhanced immune cell infiltration [11,15,19], dendritic cell activation [17,21], and increased tumor antigen cross-presentation with activation of cytotoxic T cell responses due to enhanced phagocytosis of tumor cells [7,8,22,23]. Given the involvement of CD47 in various physiological and cellular functions, multiple non-mutually exclusive mechanisms may be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Some of which selectively regulate adaptive antitumor immunity. This hypothesis was supported by functional validation experiments of several prioritized hits, including CD47 and TGFb1, which are potential targets for single or combination immunotherapy [105].…”
Section: The Use Of Functional Genomics To Understand Cancerimmune System Interactionsmentioning
confidence: 81%